Curriculum Design: Difficulties and Realities in Introducing Innovative Teaching and Learning Experience - Noordin Ayus, Abdul Mohaimin (The Indonesian Journal of International Clinical Legal Education, 2019)
The 20th century legal education system is said to have failedto teach students practical legal skills, critical analysis anddecision-making methods, as it did not give studentssystematic training in effective techniques for learning the lawfrom the experience of the legal practice. At the end of thecentury, a pedagogic method known as the clinical legaleducation was developed which broadens legal education inall of these dimensions. It is important for a member of a lawschool academic to examine this pedagogical approachtowards enhancing students’ knowledge and skills in meetingthe needs of the changing time. Law schools in Malaysia andto some extent in Brunei Darussalam have some or limitedautonomy in introducing Innovative Teaching and Learningmethods into the curriculum design, but no true success couldbe lauded either as difficulties and realities in the study of lawwithin the common law jurisdictional context requires strongcognitive elements before a student could really delve inpractical legal skill exercises. The realities cover two main areasof development: (1) the components of legal studies, and (2)the outcomes of the studies. The difficulties may be associatedwith (1) the governing educational policies; (2) qualificationand quality of students admitted to law school, (3) theexperience of the law teachers; and (4) the learningenvironment. The traditional method could not simply beblamed or ignored, if there ever be a failure in the system, onthe one hand, and the much ushered innovative learningmethods may not necessarily be the success factor, on theother.